Prospects for Professional Training for the Development of Autopedagogic Competence in Future Primary School Teachers - Petkova , Iliana; Tynyskhanova, Aiym (Pedagogy and Psychology, 2025)
This article examines the issue of forming autopedagogic competence in future primary school teachers, highlighting the significance of lifelong learning in the context of educational modernization. Special emphasis is placed on fostering teacher professionalism and self-education, which are among the key objectives of Kazakhstan’s national education development strategy. The study explores the psychological and pedagogical foundations of self-directed learning, identifying essential components of pedagogical competence and the need for continuous professional growth. Methodology and Methods. The study employed a combination of theoretical and analytical methods, including literature review and comparative analysis of contemporary pedagogical research. A qualitative assessment was conducted to evaluate current approaches to the development of autopedagogic competence, with a particular focus on teacher education practices in higher education institutions. Results. The research findings indicate that one of the primary indicators of successfully developed autopedagogic competence is the future teacher’s awareness and readiness for independent professional development. Although various studies have addressed professional development more broadly, key aspects remain insufficiently explored – particularly those relating to the personalization of teacher training, the integration of self-education strategies in university curricula, and the articulation of clear indicators of pedagogical competence specific to the primary school context. Scientific novelty. This study contributes to the theoretical understanding of autopedagogic competence by identifying its core components and the factors influencing its development. It reveals significant gaps in teacher training programs regarding the support of self-directed learning, thus offering a new perspective on how universities can structure teacher education to promote lifelong professional growth. Practical significance. The findings offer evidence-based guidance for higher education institutions aiming to prepare competitive and competent primary school teachers. By emphasizing self-education, self-reflection, and continuous development, the study supports the design of teacher training programs that align with modern educational demands and foster meaningful, sustained professional engagement.